The War-Zone Consequences of the Deformed Linguistic Image: Iraqi Simultaneous Interpreters during the US-led Invasion - Khalifah Sultan , Jasim (Journal of College of Education, 2021)
Iraqi interpreters have played a very vital role in facilitating communication between the coalition forces and local people since the US-led war in 2003. There was, however, a tendency among the locals to view them as collaborators, traitors, or spies: many were killed and many others whose life remained under serious threat by insurgents belonging to different political or sectarian groups. Disloyalty to the homeland, therefore, has been their defining attribution. Such attribution has cast its shadow over translators as well, though only a few have worked with the coalition onsite, in camps or military bases. The reason that lies behind this stereotypical attribution is solely linguistic. To the Arab world novice people, for the profession and concept of an interpreter seems new as both a translator and an interpreter are referred to by Iraqis as ‘مترجم’(mutarjim). The distinction between the two remain lexical via the post-modification elements ‘تحريري’ and ‘شفوي’ that characterize the medium written versus oral. Iraqi Print media have actively participated in glossing such linguistically deformed professional image of the translators, as news and reports typically overlooked the terminological distinction. Inspired by Charles Sanders Peirce’s (1958) theory of signs, Eleanor Rosch’s (2002) prototype theory, and Mona Baker’s (2005;2006) initiative of narrative theory in translation studies, the present paper investigates the roots, means, and possible consequences of this misconception throughout the analysis of miscellaneous national and international newspaper materials released during the US-led invasion. It has been found that local media have energetically engaged in darkening the boundaries between the two professions.
Keywords: Translators and Interpreters, the Semiotics of Sign, Prototype Theory, Narrative Theory Al-Mada, and Al-Akhbaar Newspapers